Seebeck Coefficient Measurements of Polycrystalline and Highly Ordered Metal-Organic Framework Thin Films. (15th February 2017) - Chen, Xin; Wang, Zhengbang; Hassan, Zeinab Mohamed; Lin, Pengtao; Zhang, Kai; Baumgart, Helmut; Redel, Engelbert
Abstract : In this work highly oriented Surface Anchored Metal-Organic Framework (SURMOF) films were fabricated quasi-epitaxial and were electrically characterized by Seebeck analysis and benchmarked against random polycrystalline MOF films loaded with tetracyano-quinodimethane (TCNQ) infiltration. The horizontal Seebeck coefficient of the oriented SURMOF films and the random polycrystalline MOF films parallel to the sample surface was measured and has been discussed. The isotropic random polycrystalline MOF films exhibit a high positive Seebeck coefficient of 422.32 μV/K at 350 K. However, the horizontal Seebeck coefficient of highly oriented SURMOF films fluctuates around 0 μV/K instead. Because the quasi-epitaxial oriented SURMOF films are highly anisotropic, there is no measurable horizontal carrier transport parallel to the SURMOF surface. However, in contrast to highly oriented (002) SURMOF films, the in-plane thermoelectric properties of random polycrystalline MOF films with sputtered Au contact pads could be measured due to the isotropic nature of these films. The high Seebeck coefficient of these random polycrystalline MOF films demonstrates promising application potential of MOF films in future thermoelectric and electronic devices.